Interactive E-Module for Science Learning Content: Validity and Feasibility - Sintawati, Ni Putu; Margunayasa, I Gede (International Journal of Elementary Education, 2021)
Lack of use and development of teaching materials, especially in science content, which causes learning activities not to run optimally. This study aims to develop an interactive e-module with science content that has been tested for validity. This development research uses the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. However, this research was only carried out until the development stage, the implementation and evaluation stages were not carried out due to time, resource and financial limitations caused by the current pandemic conditions. The subject in this study was an interactive e-module with science content, while the object in this study was the validity of an interactive e-module with science. This development research uses a questionnaire method by distributing assessment sheets to respondents, namely, material experts, media experts, and practitioners. The results of the validity test of the interactive e-module on the IPA content are in the form of numbers that are calculated as the average score then categorized into the five scale guideline table. The assessment of two material expert lecturers obtained an average score of 4.5 with very good qualifications. The assessment of two media expert lecturers obtained an average score of 4.8 with very good qualifications and the results of the practitioner's assessment consisting of two homeroom teachers in grade V SD obtained an average score of 4.9 with very good qualifications. Based on the results of the analysis obtained, it can be concluded that the interactive e-module with science content is very good qualifications.